Blood Plasma Proteins Associated With Heart Rate Variability in Cosmonauts Who Have Completed Long-Duration Space Missions - Pastushkova, Ludmila Kh.; Rusanov, Vasily B.; Goncharova, Anna G.; Nosovskiy, Andrei M.; Luchitskaya, Elena S.; Kashirina, Daria N.; Kononikhin, Alexey S.; Kussmaul, Anna R.; Yakhya, Yusef D.; Larina, Irina M.; Nikolaev, Evgeny N. (Frontiers in Physiology, 2021)
The study presents the results of evaluating the changes in the concentrations of blood plasma proteins associated with heart rate variability in cosmonauts who have completed space missions lasting about 6 months. The concentrations of 121 proteins were quantified in biological samples of the cosmonauts' blood plasma. The subgroups of proteins associated with the physiological processes of the heart rate variability autonomic regulation were identified using bioinformatic resources (Immunoglobulin heavy constant mu, Complement C1q subcomponent subunit C, Plasma serine protease inhibitor, Protein - 72 kDa type IV collagenase, Fibulin-1, Immunoglobulin lambda constant 3). The concentration of these proteins in the blood plasma before the flight, and the dynamics of concentration changes on the 1st and 7th days of the post-flight rehabilitation period differed in the groups of cosmonauts with a predominance of sympathetic or parasympathetic modulating autonomous influences. The dynamics of changes in the concentrations of the identified set of proteins reveal that in cosmonauts with a predominance of sympathetic modulating influences, the mechanisms of autonomic regulation are exposed to significant stress in the recovery period immediately after the completion of the space mission, compared with the cosmonauts with a predominance of parasympathetic modulating influences.